Pengembangan Transportasi Sungai untuk Mendukung Smart City - Hidayat, Bachtari; Fatoni, Agus; Saksono, Herie; Asriani; Andari, Tania (Research and Development Agency Ministry of Home Affairs, 2022)
Light Rail Transit (LRT), integrated with river transportation as a unique city and tourist attraction, is important in supporting smart cities. This study aims to assess the possibilities of river transportation users who use LRT as an advanced mode and its supporting infrastructure. This research is quantitative research with a descriptive approach. Primary data is obtained from a survey of the movement of river transportation users from outside the city to Palembang City and has the potential to continue their journey using the LRT. Interviews were also conducted with respondents covering the respondents' travel destination, travel destination, and reasons. The study results indicate that the use of river transportation from within the city, which gets off at the pier and does not continue the journey as much as 75%, and the rest will continue the journey using the LRT mode only 16%. Meanwhile, 29.5% of river transport users from outside the city disembark at the pier. The remaining 53% continue their journey with the potential to use LRT, which is a reasonably high percentage if it can be appropriately managed. The availability of a variety of public transportation that can park near the pier at a cheaper rate is the main cause of their lack of interest in using the LRT mode. The proposed supporting infrastructure for integration between river transport and LRT is the pedestrian path.